Analysis of Suspension of Clinical Trials for Drug Registration in China - Su, Xian; Pang, Xiaocong; Zeng, Xin; Gao, Yi; Cui, Yimin; Wang, Haixue (Frontiers in Pharmacology, 2021)
Suspension is an important risk control measure during clinical trials. We investigated the use of this risk control system in China and identified common reasons for suspension by we analyzing trends, hold issues, outcomes, background and design characteristics of suspended clinical drug trials since January 1, 2013. Numbers and proportion of clinical trials suspended based on benefit/risk factors have been increasing without holds on registrations by CDE. Reasons for suspension vary among trial phases, benefit and risk factors, protocol issues, investigator/research institution considerations, and supply problems. Suspensions continue for 67.35% of > 1-year trials. Children and the elderly were enrolled in 4.1% and 41% of the suspended trials, respectively. Strengthening regulation of pre-market pharmacovigilance through optimizing reporting and monitoring of safety information during clinical trial is thus needed. Establishing a closed-loop treatment mechanism for trial suspension is also important. Examination of potential risks, such as the quality of protocols, the ability of the institution to support the trial, and the adequacy of supplies of the investigational product is needed before beginning clinical trials. More careful evaluation at the registration phase will reduce the frequency of suspension and protect subjects after suspension occurs.